Kompetensi Guru Reka Bentuk dan Teknologi Sekolah Rendah Di Daerah Batu Pahat : The Competencies of Primary School Design and Technology Teachers in Batu Pahat District - Jie Sheng, Ngo; Bin Ibrahim, Badaruddin (Online Journal for TVET Practitioners, 2023)
Reka Bentuk dan Teknologi merupakan mata pelajaran yang baharu diperkenalkan pada tahun 2014, maka kompetensi guru Reka Bentuk dan Teknologi harus dititikberatkan untuk memastikan objektif mata pelajaran RBT tercapai. Kementerian Pendidikan telah menerbitkan Standard Guru Malaysia untuk meningkatkan kompetensi guru dengan mementingkan tiga standard, iaitu standard amalan nilai profesionlisme keguruan, standard pengetahuan dan kefahaman guru dan standard kemahiran pengajaran dan pembelajaran. Untuk menghasilkan murid yang mampu bersaing dan berketerampilan pada abad ke-21, guru Reka Bentuk dan Teknologi  perlu memiliki kompetensi seperti nilai, pengetahuan dan kemahiran agar tetap relevan dengan perkembangan terkini dalam pendidikan amnya dan bidang Reka Bentuk dan Teknologi khususnya. Kajian ini menggunakan pendekatan kuantitaif yang menggunakan kaedah tinjauan dengan soal selidik untuk melihat tahap kompetensi guru Reka Bentuk dan Teknologi sekolah rendah di daerah Batu Pahat. Seramai 403 orang guru Reka Bentuk dan Teknologi sekolah rendah di daerah Batu Pahat terlibat dalam kajian ini. Hasil dapatan kajian menunjukkan tahap kompetensi guru Reka Bentuk dan Teknologi  sekolah rendah di daerah Batu Pahat adalah tinggi (M=4.45, SP=0.56). Design dan Technology is a newly introduced subject in year 2014, so the competence of Design and Technology teachers should be emphasized to ensure that the objectives of the subject Design and Technology are achieved. The Ministry of Education has published the Malaysia Teacher Standards to improve the competence of teachers by focusing on three standards, namely the standard of practice values of teaching professionalism, the standard of teacher knowledge and understanding and the standard of teaching and learning skills. In order to produce students who are able to compete and have skills in the 21st century, Design and Technology teachers need to have competencies such as values, knowledge and skills in order to remain relevant to the latest developments in education in general and the field of Design and Technology in particular. This study uses a quantitative approach that uses a survey method with a questionnaire to see the level of competence of primary school Design and Technology teachers in the Batu Pahat district. A total of 403 primary school Design and Technology teachers in Batu Pahat district were involved in this study. The results of study show that the level of competence of primary school Design and Technology teachers in Batu Pahat district is high (M=4.45, SP=0.56). Highly competent teachers are needed to teach Design and Technology subjects in order to achieve the goal of the National Education Philosophy, which is to produce balanced and holistic human capital from various aspects.